Exploring Factors Influencing Learning Stress in Basic Biology Courses: Insight From Undergraduate Students in Papua - Arini Rahmadana; Adi Rahmat; Lilit Rusyati; Kusnadi Kusnadi; Mustafa Cakir (Universitas Syiah Kuala, in collaboration with the Perkumpulan Pendidik IPA Indonesia (PPII), (MoU), 2026)
Stress in studying is a common experience among undergraduate students, especially in courses that require intensive understanding such as basic biology. This study aims to identify factors that influence students' perceptions of stress. This study used a modified version of the academic stress scale developed by Bedewey and Gabriel (2015) with an internal consistency reliability of 0.7 (Cronbach's alpha). We added several statements to make them relevant to students' conditions and several open-ended questions to strengthen the data. The survey was distributed to three universities in the Papuan region with a total of 60 respondents. Participants were second- and fourth-semester students enrolled in basic biology courses. Descriptive statistics were used to analyze the students' experiences. The results showed that half of the students experienced academic stress primarily due to anxiety about course grades. Other major stress factors include feeling overwhelmed by the workload, difficulties with self-management, and limited knowledge about the learning strategies they should use. Non-academic stressors included personal and economic problems, as well as issues related to the personality of their lecturers. Students' perceptions of learning stress were in the moderate category. These findings suggest that excessive workload and poor self-management increase academic stress and may contribute to cognitive overload. Therefore, teaching strategies that consider student workload and develop self-regulation in students have the potential to reduce learning stress and improve academic well-being in biology courses